On‐Tissue Hydrogel‐Mediated Nondestructive Proteomic Characterization: Application to fr/fr and FFPE Tissues and Insights for Quantitative Proteomics Using a Case of Cardiac Myxoma. Issue 1 (12th November 2018) - Taverna, Domenico; Mignogna, Chiara; Santise, Gianluca; Gaspari, Marco; Cuda, Giovanni
Abstract : Purpose: The application of a methodology for quantitative protein analysis from formalin‐fixed and paraffin‐embedded (FFPE) tissue by using hydrogels. Miniaturized polymeric gels are placed onto histologically defined tissue regions in order to perform localized digestion for bottom‐up proteomics. Hydrogel‐extracted peptides are then labeled with tandem mass tags (TMT) reagents for relative protein quantification. A cardiac myxoma biopsy is used. Experimental design: Multiple hydrogels, incorporating the proteolytic enzyme trypsin, are placed on serial tissue sections, and processed for digestion and TMT derivatization. SCX fractionation before LC‐MS/MS analysis and bioinformatics analysis are carried out. Results: Two histologically different areas on both FFPE and frozen sections of the same cardiac myxoma biopsy are compared. In total, 1949 (FFPE) and 2491 (frozen) proteins are identified, with a total overlap of 56%. The quantitative comparison highlighted 15 (FFPE) and 138 (frozen) differentially expressed proteins between myxoma regions. Conclusion: The methodology successfully detects numerous protein signals from FFPE and frozen specimens and is able to differentiate between tissue regions. A fast and reliable tissue preparation for quantitative protein analysis by minimum sample manipulation is developed. This offers an option for on‐tissue proteomics analysis while preserving the inherent spatial information on the tissue.